Single Deepest Vertical Pocket or Amniotic Fluid Index as Evaluation Test for Predicting Adverse Pregnancy Outcome (SAFE Trial): A Multicenter, Open-Label, Randomized Controlled Trial. Issue 10 (October 2016) - Kehl, S.; Schelkle, A.; Thomas, A.; Puhl, A.; Meqdad, K.; Tuschy, B.; Berlit, S.; Weiss, C.; Bayer, C.; Heimrich, J.; Dammer, U.; Raabe, E.; et al.
Abstract : (Abstracted from Ultrasound Obstet Gynecol 2016;47:674–679) One of the important aspects of fetal well-being assessment is amniotic fluid volume, lack of which leads to oligohydramnios and consequently adverse perinatal outcomes. Amniotic fluid estimation by ultrasound can be performed by assessment of the amniotic fluid index (AFI) or the single deepest vertical pocket (SDP) technique.